Employing Flipped Classroom: A Case Study in Indonesian EFL University Context - Sya'adah, Ridha Rifa'atus; Rahmat, Rahmat; Marlina, Neni (Universitas Siliwangi, 2022)
The research in flipped classroom is gaining popularity across countries. However, there is very limited research that describes how to implement flipped classroom method in learning. This study aims to describe how to implement the flipped classroom in TELL classes. The research design of this study is case study. Then, the technique of collecting the data through email interviews. After that, the data was analysed by thematic analysis. As the result of this analysis, it was found that the implementation of flipped classroom is divided into three stages such as pre-class activities of flipped classroom, while class activities of flipped classroom, and post-class activities of flipped classroom. Moreover, while implementing flipped classroom there are such challenges that arise and how to overcome them. Key Words: Flipped Classroom, EFL, Bloom’s Taxonomy, Mastery Learning, Constructivism